Analysis of Student Learning Difficulties in Human Movement System Material - Febri Ulina Feronika Girsang; Marlinda Nilan Sari Rangkuti (UNIVERSITAS PGRI MADIUN, 2026)
This study aims to determine students' learning difficulties and the factors causing these difficulties in learning the human movement system material for Class XI at SMA Negeri 1 Silimakuta. The research population was all Class XI students who studied biology. The sample was taken using Purposive Sampling, and the method used was descriptive quantitative. The instruments used in this study were essay tests and questionnaires. Data were analyzed using a percentage technique. The results showed that:(1) The percentage of student learning difficulties at the cognitive level for knowledge (C1) questions was 50.69%, comprehension (C2) was 63.75%, application (C3) was 58.84%, analysis (C4) was 57.08%, evaluation (C5) was 67.43%, and creation (C6) was 74.44%.(2) Furthermore, the first indicator was 62,96%, the second indicator was 59,72%, the third indicator was 61,06 %, and the fourth indicator was 61.34%. (3) The factors influencing student learning difficulties were examined from both internal and external aspects. The internal factors included: interest at 76.59%, motivation at 79.99%, intelligence at 73.04%, and attention at 74.63%. The external factors included: books at 72.61%, media at 70.97%, teacher's teaching methods at 76.49%, and facilities and infrastructure at 73.83%.